Susceptibilities of Oral Bacteria and Yeast to Mammalian Cathelicidins - Guthmiller, Janet M. (American Society for Microbiology, 2001)
The effects of cathelicidins against oral bacteria and clinically important oral yeasts are not known. We tested the susceptibilities of Actinobacillus actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis, Streptococcus sanguis, Candida krusei, Candida tropicalis and Candida albicans to the following cathelicidins: FALL39, SMAP29, and CAP18. SMAP29 and CAP18 were antimicrobial, whereas FALL39 did not exhibit antimicrobial activity. Future studies are needed to determine the potential use of these antimicrobial peptides in prevention and treatment of oral infections.